The dynamic evolution of preferences - Aviad Heifetz; Chris Shannon; Yossi Spiegel (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
This paper develops a general methodology for characterizing the dynamic evolution of preferences in a wide class of strategic interactions. We give simple conditions characterizing the limiting distribution of preferences in general games, and apply our results to study the evolutionary emergence of overconfidence and interdependent preferences. We also show that this methodology can be adapted to cases where preferences are only imperfectly observed.
Keywords: 330; Präferenztheorie; Nichtkooperatives Spiel; Theorie